Tricuspid Valve Disease: Unrecognized? Undertreated? - Rizzo, Toni (MD Conference Express, 2012)
This article discusses the impact and management of tricuspid valve disease. Although much attention in clinical practice and research on patients with valvular heart disease has focused on disorders of the mitral and aortic valves, tricuspid regurgitation can also be associated with significant morbidity and mortality.